Before the wind - Lynch, Jim, 1961- (Alfred A. Knopf, 2016)
Growing up on the Puget Sound, the Johannssen family has sailing in their blood, but the oldest brother, Josh, is left puzzling over what caused his siblings to flee, one to Africa, the other to points unknown as a fugitive and pirate.